SARS-CoV-2 vaccine effectiveness and clinical outcomes in hemodialysis patients: the NHIS-COVID-19 cohort study in South Korea - Lee, Young-Ki; Jeong, Seon A.; Park, Hayne Cho; Kim, Do Hyoung; Yoo, Kyung Don; Yoon, Hye Eun; Kim, Yang Gyun; Cho, Ajin (Frontiers in Public Health, 2024)
Background Patients undergoing hemodialysis (HD) have a high risk of novel coronavirus disease 2019 (COVID-19) and poor clinical outcomes. This study aimed to investigate severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccine effectiveness against infection and deaths in the South Korean population undergoing HD. Methods We conducted a retrospective cohort study to compare the incidence of COVID-19 and post-diagnosis mortality between patients who were either never vaccinated or fully or partially vaccinated. The Korean nationwide COVID-19 registry and the Korean National Health Insurance Service databases were used. Adult patients without a history of COVID-19 were included between October 8, 2020, and December 31, 2021. The study outcomes were COVID-19 diagnosis, severe clinical COVID-19-related events, and post-diagnosis death. Results Eighty-five thousand eighteen patients undergoing HD were included, of whom 69,601 were fully vaccinated, 2,213 were partially vaccinated and 13,204 were unvaccinated. Compared with the unvaccinated group, the risk of being diagnosed with COVID-19 in patients who were fully vaccinated decreased during the study period (adjusted odds ratio [aOR] = 0.147; 95% confidence interval [CI] = 0.135–0.159). There were 1,140 (1.3%) patients diagnosed with COVID-19. After diagnosis, fully vaccinated patients were significantly less likely to die than unvaccinated patients (aOR = 0.940; 95% CI = 0.901–0.980) and to experience severe clinical events (aOR = 0.952; 95% CI = 0.916–0.988). Conclusion Full vaccination against COVID-19 was associated with a reduced risk of both infection and severe clinical outcomes in the South Korean population undergoing HD. These findings support the use of vaccination against SARS-CoV-2 among patients undergoing HD.